Integrasi Wahyu dan Akal dalam Kitab Al-Hikmah fii Makhlukatillah Terhadap Perkembangan PAI di Era Modern - Juniari Tri Sutrisno; Sumanta Sumanta; Meiza Fajar Akbar; Anam Khoirul Rozak (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This article is motivated by the phenomenon of increasing complexity in Islamic Religious Education (IRE) challenges in the modern era, particularly due to the rapid pace of modernization, scientific developments, and technology, which often give rise to a dichotomy between normative religious approaches and critical rationality. This condition requires an IRE paradigm that is capable of integrating revelation as a source of transcendent values with reason as a human intellectual instrument. This study aims to analyze the concept of the integration of revelation and reason in Imam Al-Ghazali's book Al-Hikmah fī Makhlūqātillāh and examine its relevance to the development of IRE in the modern era. The research method used is a qualitative approach through library research with data collection techniques in the form of primary and secondary text analysis, analyzed using content analysis and thematic analysis within the framework of Islamic education epistemology. The results of the study show that Al-Ghazali places revelation and reason as two complementary sources of knowledge that are not dichotomous, resulting in a holistic, critical, and contextual understanding of religion. This integration is proven to be relevant in strengthening the philosophical foundations of PAI, encouraging reflective learning, and bridging religious and general knowledge without losing spiritual and moral orientation.